2010
DOI: 10.1002/elps.200900394
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin–liposome interactions: Characterization of liposomal formulations of an acylated 28‐amino acid peptide using CE

Abstract: Ghrelin is a pharmacologically interesting peptide hormone due to its effects on appetite and metabolism. The cationic, octanoylated 28 amino acid peptide has a short biological half-life; thus, prolonged release formulations are of interest. Acylated peptides have been suggested to bind to or be incorporated into liposomes. Formulations based on neutral dipalmitoylphosphatidylcholine (DPPC) liposomes and phosphatidylcholine:cholesterol (70:30 mol%) liposomes, and negatively charged dipalmitoylphosphatidylchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…In both theoretical localizations, the octanoyl fatty-acid group is inserted in the lipid structure. This interaction has already been described in other studies, 37,38 and shown to provide significant protection to the octanoyl group, which is essential for preserving the physiological activity of Ghrl. 34 …”
Section: Isothermal Titration Calorimetrymentioning
confidence: 76%
See 1 more Smart Citation
“…In both theoretical localizations, the octanoyl fatty-acid group is inserted in the lipid structure. This interaction has already been described in other studies, 37,38 and shown to provide significant protection to the octanoyl group, which is essential for preserving the physiological activity of Ghrl. 34 …”
Section: Isothermal Titration Calorimetrymentioning
confidence: 76%
“…36,37 However, when looking at EE, it can be seen that electrostatic interactions have a clear impact in the case of Ghrl. 38 By providing a negative charge to ALs, the percentage of Ghrl loaded in ALs was fivefold higher compared to CLs (Table 2). This resulted in EE of 56.1%±7.8%, 21.3%±4.1%, and 9.8%±3.7% for ALs, NLs and CLs, respectively.…”
Section: Droplet-size Distributionmentioning
confidence: 99%
“…Interactions of ghrelin, a pharmacologically interesting appetite‐stimulating peptide hormone, with neutral dipalmitoylphosphatidylcholine liposomes and negatively charged phosphatidylcholine/cholesterol (70/30 mol%) liposomes were investigated by CZE with UV‐detection at 200 nm in BGE containing 10 mM HEPES and 50 mM KCl, pH 5.50 241, 242. About 75% cationic ghrelin was bound to anionic phosphatidylcholine/cholesterol (70/30 mol%) liposomes but only 5–10% was bound to neutral dipalmitoylphosphatidylcholine liposomes.…”
Section: Applicationsmentioning
confidence: 99%
“…To note is that the drug to liposome interactions were found to depend on the drug concentrations and neutral drugs could not be analyzed by CE‐FA due to co‐elution with the EOF. The potential of CE to study a liposomal drug formulation was revealed in . Interactions of the 28 amino acid peptide ghrelin and its n ‐octanoyl analogue with neutral 1,2‐dipalmitoyl‐ sn ‐glycero‐3‐phosphocholine (DPPC), DPPC/cholesterol, and net negative DPPC/1,2‐dipalmitoyl‐ sn ‐glycero‐3‐phospho‐L‐serine liposomes were investigated by CE‐FA using fused silica, poly(dimethyldiallylammonium chloride), and poly(vinyl alcohol)‐coated capillaries.…”
Section: Liposomes In Ekc Pf‐ekc and Ce‐famentioning
confidence: 99%
“…In this section, we will go through studies where liposomes prepared from different kinds of phospholipids and cholesterol have been applied in interaction studies with compounds. The techniques include conventional EKC , PF‐EKC , and CE‐FA .…”
Section: Liposomes In Ekc Pf‐ekc and Ce‐famentioning
confidence: 99%